The Road to Recovery: A Two-Year Longitudinal Analysis of Mental Health Among University Students During and After the COVID-19 Pandemic - Rosie E. Allen; Kevin D. Hochard; Chathurika Kannangara; Jerome Carson (Behavioral Sciences)
Longitudinal research into the impact of COVID-19 on university students’ mental health beyond the pandemic is lacking. This study aims to address the gap in the literature by tracking the mental health of university students over a two-year period, spanning the COVID-19 pandemic and its aftermath. A two-year longitudinal study surveyed a sample of university students (n = 302) three times between May 2020 and May 2022. Students’ psychological distress, generalised anxiety, flourishing, and personal wellbeing were assessed at each time point. It was found that students’ psychological distress levels spiked in May 2021 (T1) during the first year of the pandemic but reverted back to similar levels seen in May 2020 (T0) at the two-year follow-up (T2). While generalised anxiety gradually improved, both students’ psychological distress and generalised anxiety remained considerably worse than pre-pandemic norms obtained in other studies. Students’ flourishing scores remained very low, while their life satisfaction and state happiness improved slightly between May 2021 (T1) and May 2022 (T2). These findings clearly demonstrate that students’ mental health is still in crisis, even after the COVID-19 pandemic. More needs to be done to support students beyond the pandemic generally, including this particularly unique cohort of students who endured unprecedented challenges for prolonged periods, and who are now transitioning into the working world. Practical implications and recommendations are discussed.